2004
DOI: 10.1177/088840640402700406
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers for Family Centered Services: A Survey of Preservice Curriculum Content

Abstract: A family-centered approach is recommended as best practice in the field of early intervention. However, recent research suggests that some professionals in the field do not always implement family-centered services. This study investigated the content taught to pre-service early intervention/early childhood special education students regarding family-centered services. Eighty-two faculty members from institutions of higher education across the U.S. rated the importance of and the extent to which they taught fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In the United States (though not in Spain), the training plans of future professionals, for example, have begun to include content that is closely related to the new paradigm (Bruder & Dunst, 2005; Prelock & Deppe, 2015; Rupiper & Marvin, 2004): (a) knowledge about families from the perspective of systems theory, (b) design and application of individualized family service plans (IFSPs), (c) respect for family and cultural diversity, (d) communication skills, and (e) teamwork. Nonetheless, these authors note that a great deal remains to be done to ensure a preservice education in EI that applies the principles of an FCA in each and every one of its disciplines (Catalino, Chiarello, Long, & Weaver, 2015; Reeves, Goldman, Burton, & Sawatzky-Girling, 2010; Stayton, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States (though not in Spain), the training plans of future professionals, for example, have begun to include content that is closely related to the new paradigm (Bruder & Dunst, 2005; Prelock & Deppe, 2015; Rupiper & Marvin, 2004): (a) knowledge about families from the perspective of systems theory, (b) design and application of individualized family service plans (IFSPs), (c) respect for family and cultural diversity, (d) communication skills, and (e) teamwork. Nonetheless, these authors note that a great deal remains to be done to ensure a preservice education in EI that applies the principles of an FCA in each and every one of its disciplines (Catalino, Chiarello, Long, & Weaver, 2015; Reeves, Goldman, Burton, & Sawatzky-Girling, 2010; Stayton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These programs should be aimed at developing the profile of a professional who understands that families are systems, is aware of the factors and processes affecting the family group dynamic, and is capable of leading processes to discuss and search for solutions to the problems facing families (Rupiper & Marvin, 2004). Programs should also train professionals in the implementation of the collaborative role (Woods & Lindeman, 2008), involve families in the process of assessing and identifying needs without feeling judged, understand and respond to the specific needs of different cultures, and recognize and support the development of families’ skills and strengths (Miller & Stayton, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In order to establish the amount of family-centered content taught in early childhood teacher preparation programs, Rupiper and Marvin (2004) surveyed 82 institutions across the United States. Results demonstrated that familycentered content was infused across course curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…2 Spring 2008 children. This experience can be critical for the implementation of family-centered practices based on a respectful collaboration with parents (Rupiper & Marvin, 2004). Parents of children with special needs often express their dissatisfaction and distrust from their experiences with professionals (Mittler, 1995;Stoner et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…With these considerations in mind, we assumed that the involvement of undergraduate special education teachers with families with children with special needs could be a meaningful pathway for their professional preparation. The collaboration of teachers with families is a recommended practice in special education (Turnbull & Turnbull, 1997) and building links with families has been suggested as a prerequisite step for preparing competent educators (Able-Boone, Crais, & Downing, 2003;Rupiper & Marvin, 2004). Also, preservice teachers visiting students at their homes gained valuable insights of the parents' role in children's learning and behaviour (Peralta-Nash, 2003).…”
mentioning
confidence: 99%